The role of teichoic acids of bifidobacteria in driving the interaction with the human host - Longhi, Giulia; Vergna, Laura Maria; Lugli, Gabriele Andrea; Bianchi, Massimiliano Giovanni; Tarracchini, Chiara; Milani, Christian; Turroni, Francesca; Bussolati, Ovidio; van Sinderen, Douwe; Ventura, Marco (Frontiers in Microbiology, 2025)
An in silico survey carried out in this study, performed on more than 3,000 publicly available bifidobacterial genome sequences, revealed clear differences in genes predicted to be involved in teichoic acid (TA) biosynthesis at inter-species level, indicating that only a small number of species possess a specific cluster for the production and assembly of these cell envelope-associated structures. Among these, Bifidobacterium bifidum represents a key member of the human gut microbiota at the early stages of life. Here, we show differences in the transcriptomic profiles of genes predicted to be involved in TA biosynthesis of three different strains of B. bifidum PRL2010 following exposure to human intestinal epithelial cells, suggesting a strain-specific and host-mediated molecular response. Notably, such data were further corroborated by in vitro experiments with isogenic derivatives of B. bifidum PRL2010 carrying mutations located in one of the genetic loci putatively responsible for TA synthesis, which suggests that TAs of PRL2010 are involved in establishing microbe-host cross talk by modulating adhesion to epithelial intestinal cells, as well as by affecting the interaction with human macrophages. We furthermore revealed that some of the key genes implicated in TA synthesis by PRL2010 are overexpressed under in vivo conditions when the microorganism is colonizing the murine gut, which further confirms a host modulatory effect on the production of these extracellular structures in bifidobacteria.